2007
DOI: 10.1002/app.26864
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene fibers containing dispersed clays having improved fire performance. I. Effect of nanoclays on processing parameters and fiber properties

Abstract: While the present interest in the use of functionalized nanoclays as additives for improving tensile properties and fire performance in polypropylene thermoplastics has led to a considerable literature, little attention has been given to this polymer in fiber form. In this article, we report the conditions necessary for and the characteristics of filaments and tapes comprising dispersions of functionalized clay in polypropylene-clay prepared by melt compounding polypropylene in a twin screw extruder. A small f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 15 publications
(22 reference statements)
2
47
0
Order By: Relevance
“…In Part 1, we demonstrated that as, has been generally demonstrated in the literature for a number of polymers [19], the addition of a small quantity of clay to PP fibres and fabrics improves the fire performance properties by lowering PHRR values [2]. In Part 2, we extend the work and report the burning behaviour of knitted fabrics produced from polypropylene fibres comprising several dispersed nanoclays and compatibilising copolymers in the presence of ammonium polyphosphate (APP) as a model conventional flame retardant.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…In Part 1, we demonstrated that as, has been generally demonstrated in the literature for a number of polymers [19], the addition of a small quantity of clay to PP fibres and fabrics improves the fire performance properties by lowering PHRR values [2]. In Part 2, we extend the work and report the burning behaviour of knitted fabrics produced from polypropylene fibres comprising several dispersed nanoclays and compatibilising copolymers in the presence of ammonium polyphosphate (APP) as a model conventional flame retardant.…”
Section: Introductionmentioning
confidence: 58%
“…In our previous communication [2] the MFI for PP after one passage through the twin screw extruder extruder has been reported as 36.0g/600s. The increase in MFI is a measure of polymer degradation induced by one extra thermal cycle [2].…”
Section: Materials Physical Properties -Melt Flow Index and Rheologymentioning
confidence: 90%
See 2 more Smart Citations
“…Nanoparticles, such as montmorillonite clay (MMT), normally reinforce the mechanical and thermal properties of nanocomposite fiber [24][25][26][27][28][29][30]. The dyeing of PLA fiber using nanoclay holds promise for the industry.…”
Section: Introductionmentioning
confidence: 99%